Characteristics of Energetic Electrons Near Active Magnetotail Reconnection Sites: Tracers of a Complex Magnetic Topology and Evidence of Localized Acceleration. Issue 2 (26th January 2021) - Turner, Drew L.; Cohen, Ian J.; Bingham, Samuel T.; Stephens, Grant K.; Sitnov, Mikhail I.; Mauk, Barry H.; Denton, Richard E.; Leonard, Trevor W.; Fennell, Joseph F.; Blake, J. Bernard; Torbert, Roy B.; Burch, James L.
Abstract: We present detailed observations and reconstructed magnetic field topologies from a magnetic reconnection event observed directly by NASA's Magnetospheric Multiscale (MMS) mission. Comparing and contrasting energy and angular distributions of >50 keV electrons observed by three MMS spacecraft separated by only ∼18 km revealed a combination of chaotic motion and surprisingly coherent gyrophase bunching within a few thousand kilometers of the reconnection site. Such gyrophase‐bunched electrons have not been observed previously at these energies in relation to magnetic reconnection. Results indicate that the magnetic topology around the electron diffusion region was relatively stable over several seconds (i.e., more than a thousand electron gyro‐periods), and the observed gyrophase bunching may be the highest‐energy extent of coherent gyrophase structures observed at lower‐energies closer to the reconnection site. We hypothesize that the coherent gyrophase bunching was evidence of these energetic electrons being accelerated at the reconnection site and possibly also in the outflowing exhaust jets of the active reconnection. This case study exemplifies how energetic electrons can carry coherent signals of remote magnetic topologies and processes relevant to the physics of magnetic reconnection. Plain Language Summary: We examined data from NASA's Magnetospheric Multiscale mission to study how very energetic electrons behave near special sites where magnetic field lines break and merge back together, altering the topology of the magnetic field. We found unexpected features in the electron distributions that indicate how the changing magnetic topology might result in coherent scattering and acceleration of those electrons Key Points: Combo of chaotic and coherent >50 keV electron motion observed near active reconnection site in Earth's magnetotail Energetic electrons can carry coherent signals of remote magnetic topologies and processes relevant to the physics of magnetic reconnection Coherent, gyro‐phase bunching in outflow exhaust very near the electron diffusion region may indicate relativistic electron acceleration